Enhancing the performance of transparent conductive oxide-less back contact dye-sensitized solar cells by facile diffusion of cobalt species through TiO2 nanopores. Issue 40 (5th April 2016) - Molla, Md. Zaman; Kawano, Minobu; Baranwal, Ajay K.; Pandey, Shyam S.; Ogomi, Yuhei; Ma, Tingli; Hayase, Shuzi
Abstract : TCO-less DSSC using cobalt electrolyte in a novel device structure is proposed. Dye surface passivation of TiO2 nanoparticle (TN) spacer boosts bulky Co 3+ ion diffusion. Dramatic enhancement in DSSC performance for dye surface passivated TN spacer. Abstract : We report a back contact (BC) transparent conductive oxide (TCO)-less dye-sensitized solar cell (DSSC) fabricated utilizing a Co 2+/3+ redox shuttle based electrolyte. A new strategy has been proposed for the reduction of the electrolyte layer by coating with a TiO2 nanoparticle spacer (TN spacer) with controlled thickness. The negatively charged TN spacer was found to decrease the diffusion of cobalt species through the TN spacer due to electrostatic interactions leading to a hampered photoconversion efficiency of 4.41%. This sluggish diffusion of bulky cobalt ions was amicably facilitated by passivating the negatively charged TN spacer surface with dye molecules. Facile transport of electrolyte ions in the nanopores of the passivated TN spacer was further confirmed by electrochemical impedance spectroscopy and estimation of the diffusion of Co 3+ species in the nanopores of the passivated TN spacer using cyclic voltammetry. The TCO-less BC-DSSC in combination with the cobalt electrolyte fabricated in this novel device architecture exhibits a significantly improved photoconversion efficiency of 6.42% after the TN spacer was passivated with the porphyrin-based dye YD2-o-C8.